Pemerolehan Kalimat Bahasa Indonesia Anak Usia 3;0-4;0 Tahun - Yuniarsih, Dwi; Ermanto, Ermanto; Emidar, Emidar (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This article was written to (1) to describe any kind of sentencein terms of syntactic form sobtained bythe child at age 3;0-4;0, and (2) describe patterns of sentences in terms of syntactic function obtained by children at age 3;0-4;0. The data of this study is the sentence that speech children aged 3;0-4;0. The data source of this research his the speech of children aged 3;0-4;0. Data obtained using methods refer to and supported by observation and recording techniques. Data obtained transcribed into written language, identified, classified, and then made conclusions. The findings of this study are the types of sentences in terms of syntactic forms found as many as four types of sentences and sentence patterns found in terms of syntactic function as much as 23 sentence patterns.